Acute and chronic effects of kisspeptin‐54 administration on GH, prolactin and TSH secretion in healthy women. (25th June 2014) - Jayasena, Channa N.; Comninos, Alexander N.; Narayanaswamy, Shakunthala; Bhalla, Sanjana; Abbara, Ali; Ganiyu‐Dada, Zainab; Busbridge, Mark; Ghatei, Mohammad A.; Bloom, Stephen R.; Dhillo, Waljit S.
Summary Background The peptide hormone kisspeptin is essential for human reproduction, acting on the hypothalamus to stimulate gonadotrophin‐releasing hormone (GnRH) secretion. Kisspeptin is currently being evaluated as a novel therapeutic for women with infertility. However, some animal studies suggest that kisspeptin may also stimulate growth hormone (GH), prolactin and thyroid‐stimulating hormone (TSH) secretion, with implications for its safety; no previous study has investigated whether kisspeptin stimulates these pituitary hormones in humans. Aim To determine whether kisspeptin‐54 modulates GH, prolactin and TSH secretion in healthy women. Design and participants Prospective, single‐blinded, placebo‐controlled, one‐way crossover study. Five healthy women received 7 days of twice‐daily subcutaneous bolus vehicle (month 1) or 6·4 nmol/kg kisspeptin‐54 (month 2). Measurements Serum samples were analysed post hoc for GH, prolactin and TSH. Results Mean serum GH, PRL and TSH did not change during the first 4 h following kisspeptin‐54 injection when compared with vehicle. The mean frequency or amplitude of GH pulses (which influence GH function) did not change acutely following kisspeptin‐54 injection when compared with vehicle. No chronic changes in serum GH, PRL or TSH were observed over the 7‐day period of twice‐daily kisspeptin‐54 injections when compared with vehicle. Conclusion While we cannot exclude any effect of kisspeptin‐54 on GH, prolactin or TSH secretion, we observed no significant changes in these hormones at a dose of kisspeptin‐54 administration known to stimulate gonadotrophin secretion in a small study of healthy women. These data have important implications for the potential of kisspeptin to treat patients with infertility.